2022
DOI: 10.3390/w15010147
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Occurrence and Cycling in the Aquatic Environment: A Comparison between Freshwater and Seawater

Abstract: Owing to the toxicity and adverse effects of arsenic on human health, its levels in aquatic environments are among the most serious threats to humans globally. To improve our understanding of its occurrence and cycling in aquatic environments, herein we review the concentration, speciation, and distribution of arsenic in freshwater, seawater, and sediments. Many natural processes, such as rock weathering and geothermal activities, contribute to the background arsenic concentrations in the natural environment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 157 publications
0
9
0
Order By: Relevance
“…The PCA indicated that both environmental matrices may be acting as a potential source of contamination, suggesting that Hg and As may be readily available for uptake by fish. Both contaminants when present in the water column can be readily absorbed by the muscle tissues of organisms through the digestion process (Williams et al, 2010;Wang et al, 2023). In particular, in the aquatic environment inorganic As is absorbed by organisms, and then methylated to organic forms through different removal pathways that return arsenic to the water column, i.e., organic As concentrations may increase, due to the microbial activity present in the water (Azizur Rahman et al, 2012).…”
Section: Mercury Species and As Concentrations In Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCA indicated that both environmental matrices may be acting as a potential source of contamination, suggesting that Hg and As may be readily available for uptake by fish. Both contaminants when present in the water column can be readily absorbed by the muscle tissues of organisms through the digestion process (Williams et al, 2010;Wang et al, 2023). In particular, in the aquatic environment inorganic As is absorbed by organisms, and then methylated to organic forms through different removal pathways that return arsenic to the water column, i.e., organic As concentrations may increase, due to the microbial activity present in the water (Azizur Rahman et al, 2012).…”
Section: Mercury Species and As Concentrations In Fishmentioning
confidence: 99%
“…Toxic metal pollution has been recognized as one of the global environmental challenges of greatest concern because it threatens human and wildlife (WHO, 2008). The presence of toxic metals, such as mercury (Hg) and metalloids such as arsenic (As), has increased considerably in aquatic systems around the world driven by anthropogenic activities such as agriculture and mining (UNEP, 2017; Wang et al, 2023). For Latin America and the Caribbean, it has been reported that small-scale artisanal mining was responsible for 29% of the Hg emissions released into the atmosphere in 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known, however, that seasonal changes in the physicochemical conditions in the river themselves, like redox condition changes of iron-oxide particles of the sediment, which is temperature driven, may contribute to the release of diluted arsenic from the riverbed sediments (Mok 1989). It has also been suggested in the literature that bacterial reduction of As(V) to more soluble species As(III), favored by warmer temperature, may be a main process controlling the seasonal variations of dissolved As concentrations (Masson 2007, Wang 2023. The Arsenic's national interannual -values timeseries is displayed in Figure 26, plotting both the full set of data, and those values excluding the LB basin, in order to check if the important change in the sites number in this basin influences the whole picture.…”
Section: Temporal Variations Of the Contamination Indicatorsmentioning
confidence: 99%
“…In China, the scale of the integrated rice–fish farming industry has steadily increased, with the farming area exceeding 39 million acres and a yield of over 3.5 million tons in 2021 [ 6 ]. However, there are widespread toxic As substances, such as arsenite, in the rice field environment [ 7 ]. Issues such as high detection rates of As in aquatic products and dietary risks have gradually attracted widespread attention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%